The Relationship Between Blood Glucose Level and other Biomarkers in Pregnant Women - Al-Quraghuli, Abdullah Zaidan Khalaf (American Journal of Biology and Natural Sciences, 2025)
This study aimed to determine the relationship between blood glucose levels and other biomarkers in pregnant women compared to non-pregnant women. This study was conducted in Kirkuk, northern Iraq, from January 2024 to April 2024. One hundred blood samples were collected and divided into two groups: 50 samples from non-pregnant women and 50 samples from pregnant women. The study revealed significant elevations in blood glucose, urea, and chloride levels in pregnant women, while serum potassium levels decreased significantly. The study did not reveal any statistically significant differences in serum potassium and creatinine levels between the two groups. These findings highlight changes in glucose metabolism, kidney function, and electrolyte balance during pregnancy, which are critical factors for fetal growth and development. Continuous monitoring of these parameters is crucial to maintaining maternal health and avoiding complications. Future studies require analyzing larger and more diverse populations, using advanced and cost-effective methods, to confirm and improve these findings.